1967
DOI: 10.1063/1.1711859
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of the Vacuum-Ultraviolet Photolysis of Matrix-Isolated HCN and Halogen Cyanides. Infrared Spectra of the Species CN and XNC

Abstract: Yes, since V does not have sites both in X and Z, it must be a subfigure of XV, YZ, or both. To be specific, suppose V is a subfigure of XV. By hypothesis PIV} is consistent with PIXY}, and we have shown that PIXY} is consistent with P{U}. Therefore, since V is a subfigure of XV, which in turn is a subfigure of U, it follows that P{ V} is consistent with P{U}=P{XY}P{YZ}/P{ V}. Statement (b) is proven by noting P{ U} = P{XYZ} = P{ Y} Py{XZ} and P{ U} = P{ X Y} P{ YZ} / P{ Y} = P { Y} Py{ X} Py{Z} ;thus Py{XZ} =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
52
1
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(71 citation statements)
references
References 11 publications
17
52
1
1
Order By: Relevance
“…Indeed, as it has been already reported for HCN and HC 3 N which can be converted into CNH 19 and CCCNH 20 by VUV irradiation, in the same way we observed that solid NH 2 CN leads to monomer HNCNH trapped in solid NH 2 CN (Figure 2). The outcome is that the band at 2125 cm -1 grows at the beginning of the UV process and then decreases when the amount of carbodiimide becomes higher in the sample.…”
supporting
confidence: 84%
“…Indeed, as it has been already reported for HCN and HC 3 N which can be converted into CNH 19 and CCCNH 20 by VUV irradiation, in the same way we observed that solid NH 2 CN leads to monomer HNCNH trapped in solid NH 2 CN (Figure 2). The outcome is that the band at 2125 cm -1 grows at the beginning of the UV process and then decreases when the amount of carbodiimide becomes higher in the sample.…”
supporting
confidence: 84%
“…15. That we see nitrile-to-isonitrile conversions in N 2 is not surprising, as they have been observed in rare-gas matrices (e.g., Milligan and Jacox, 1967). Less expected is that these reactions also Fig.…”
Section: Reaction Productsmentioning
confidence: 80%
“…26,27 They are however shifted by À88.0 and +25.5 cm À1 (À65.0 and +17.5/17.0 for solid nitrogen), respectively, relative to the positions of the HCN monomer absorptions. The observed shifts strongly suggest that these bands originate from complexed hydrogen cyanate molecules.…”
Section: Resultsmentioning
confidence: 98%